176 Andexanet Alfa: An Investigational Universal Antidote for Reversal of Anticoagulation of Factor Xa Inhibitors in Healthy Human Volunteers. (August 2016) - Mar, Florie; Crowther, Mark; Gold, Alex; Lu, Genmin; Leeds, Janet; Wiens, Brian; Mathur, Vandana; Castillo, Janice; Conley, Pamela; Connolly, Stuart; Curnutte, John
Abstract : INTRODUCTION: Direct FXa inhibitors have demonstrated convincing anticoagulant efficacy. However, risk of major bleeding is a concern and no specific antidotes are available for reversal. Andexanet alfa (AnXa), a recombinant modified FXa, is an investigational specific antidote for FXa inhibitors. We report data from the ANNEXA"! Phase 3 registration studies in older healthy subjects anticoagulated with apixaban (apix) or rivaroxaban (riva). METHODS: ANNEXA A&R were 2 phase 3, randomized, double-blind, placebo-controlled studies of AnXa in healthy subjects age 50 to 75 administered either apixaban or rivaroxaban. Andexanet dose selection was based on phase 2 data and PK/PD modeling, which will be presented. In ANNEXA"!-A, subjects were treated with apix 5 mg twice daily for 4 days to achieve steady-state concentrations. AnXa (Part 1: 400 mg bolus; Part 2: 400 mg bolus plus 4 mg/min × 2-hour infusion) or placebo was administered on day 4, 3 hours after the last apix dose. In ANNEXA"!-R, subjects were treated with riva 20 mg every day for 4 days to achieve steady-state concentrations. AnXa (part 1: 800 mg bolus; part 2: 800 mg bolus plus 8 mg/min × 2-hour infusion) or placebo was administered on day 4, 4 hours after the last riva dose. Safety data were collected through day 43. RESULTS: ANNEXA-A&R enrolled 63 and 82 subjects, respectively. The primary efficacy end point, percent change from baseline in anti-FXa activity to nadir (part 1: between 2 and 5 minutes postbolus; part 2: between 10 minutes before and 5 minutes after the end of the continuous infusion) was met for each part with high statistical significance ( P < .001 vs placebo). Additional efficacy end points, including reduction in plasma free inhibitor concentration and restoration of thrombin generation, were also met. There were no serious adverse events, thrombotic events, or antibodies to FX or FXa. The andexanet PK/PD model accurately predicted the riva and apix anti-FXa activity observed in this study. CONCLUSION: ANNEXA-A&R achieved all primary and secondary end points with high statistical significance. AnXa treatment resulted in rapid and sustained reversal of both apix- and riva-induced anticoagulation. A phase 3b/4 confirmatory study (ANNEXA-4) in patients with acute major bleeds is ongoing.